Peningkatan Produktivitas Tanaman di Lahan Rawa Melalui Aplikasi Teknologi Budidaya Modern dengan Metode Raised Bed Gardening Bagi Masyarakat Asli Papua di Wasur: Pengabdian - Nina Maksimiliana Ginting; Paulus Peka Hayon; Nurhaya Jahidin Panga; Febri Nur Pramudya; Abdul Rizal; Maria M.D Widiastuti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Wasur Village is dominated by indigenous Papuans, most of whom remain underprivileged. The majority work in the informal sector, such as hunting, laboring, carpentering, or fishing, with minimal and uncertain incomes, making it difficult to improve their standard of living. Their low level of education and skills makes it difficult for them to enter the formal sector. Agriculture has the potential to improve welfare by not only reducing poverty but also improving nutrition, health, environmental quality, entrepreneurship, and equality. Therefore, the active role of Musamus University, as the only state university in South Papua, is crucial in improving the knowledge and skills of the Wasur Village community. One approach offered is Raised Bed Gardening, a method of growing crops in raised beds. This method offers the benefits of better soil quality, optimal drainage, and easy maintenance. In the swampy areas of Wasur Village, this method allows for repeated land use, prevents flooding during the rainy season, and facilitates plant care.